Renal Pseudoaneurysms and Arteriovenous Fistulas as a Complication of Nephron-Sparing Partial Nephrectomy: Technical and Functional Outcomes of Patients Treated With Selective Microcoil Embolization During a Ten-Year Period - Strobl, F. F.; D'Anastasi, M.; Hinzpeter, R.; Franke, P. S.; Trumm, C. G.; Waggershauser, T.; Staehler, M.; Clevert, D. A.; Reiser, M.; Graser, A.; Paprottka, P. M. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Purpose: The aim of this study was to evaluate the clinical and functional outcomes in patients who underwent selective interventional embolization of renal pseudoaneurysms or arteriovenous fistulas at our center.Materials and Methods: Our retrospective analysis included all consecutive patients who received selective transcatheter embolization of renal pseudoaneurysms or arteriovenous fistulas after partial nephrectomy in our department from January, 2003 to September, 2013. The technical and clinical success rate and functional outcome of every procedure was collected and analyzed. Furthermore, the change in renal parenchymal volume before and after embolization was determined in a subgroup.Results: A total of 1425 patients underwent partial nephrectomy at our hospital. Of these, 39 (2.7 %) were identified with a pseudoaneurysm or an arteriovenous fistula after partial nephrectomy. The diagnosis of the vascular lesions was made by means of biphasic CT or CEUS. Technical success by means of selective microcoil embolization was achieved in all 39 patients (100 %). Clinical success, defined as no need for further operation or nephrectomy during follow-up, was achieved in 35 of 39 patients (85.7 %). Renal function, as measured by eGFR before and after the intervention, did not change significantly. However, a mean loss of parenchymal volume of 25.2 % was observed in a subgroup. No major or minor complications were attributable to the embolization procedure.Conclusion: Transcatheter embolization is a promising method for treating vascular complications which may occur after partial nephrectomy. We confirm the high success rate of this technique while discussing renal functional outcomes and potential safety aspects.Key points:• Arterial pseudoaneurysms and arteriovenous fistulas are rare but severe complications after partial nephrectomy• Selective microcoil embolization is a safe and effective kidney-preserving procedure for treating these complications• Embolization leads to a significant loss of renal parenchymal volume but not to a loss of renal functionCitation Format:• Strobl FF, D'Anastasi M, Hinzpeter R et al. Renal Pseudoaneurysms and Arteriovenous Fistulas as a Complication of Nephron-Sparing Partial Nephrectomy: Technical and Functional Outcomes of Patients Treated With Selective Microcoil Embolization During a Ten-Year Period. Fortschr Röntgenstr 2016; 188: 188 – 194
Keywords: embolization; renal arteries; angiography; interventional procedures